(3EOGQI JcfhdhLjG GdeYdheGJ (B/s - (3GdWjWj, NVQ eUHGMs; (3jGZj, GMSGf eMeOs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2012)
(3EOGQI GdeDSSGJ GdQbejI (B-(3JcfhdhLjG GdGfJQfJ (B-(3EOGQI GdGYeGd hGdJLGQI GdGdcJQhfjI (B-(3GdhXGFa GdGOGQjI hGSGSjGJ GOGQI GdeTGQjY (B-(3GOGQI GdJZjjQ (B-(3GOQGI GdLhOI (B-(3GSJNOGe JbfjI GdeYQaI aj JMSjf GOGQI GdJZjjQ (B-(3GdJYdje GdGdcJQhfj (B-(3GdJShjb YHQ GdGfJQfJ (B-(3GOGQI SdSdI GdGeOGO (B-(3GOGQI GdYdGbI eY GdRHhf GdcJQhfjG (B-(3GOGQI GfXeI Gef GdMGShH (B-(3GdeSGFd GdbGfhfjI hGdGNdGbjI aj GdGYeGd GdOhdjI hGdGdcJQhfjI (B-(3GdbGfhf GdOhdj ddJLGQI GdGdcJQhfjIs
Keywords: (3GdEOGQI GdYdejIs; (3JbfjGJ GdEOGQI (B- (3JcfhdhLjGs; (3JcfhdhLjG GdeYdheGJs